1998
DOI: 10.1007/s002590050254
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and dosimetry of iodine-123 labelled PE2I in humans, a radioligand for dopamine transporter imaging

Abstract: The iodine-123 labelled selective ligand N-(3-iodoprop-2E-enyl)-2-beta-carbomethoxy-3beta-(4-methylphenyl) nortropane ([123I]PE2I) was evaluated as a probe for in vivo dopamine transporter imaging in the human brain. Six healthy subjects were imaged with a high-resolution single-photon emission tomography scanner. Striatal radioactivity peaked at 1 h after injection. The background radioactivity was low. The volume of distribution in the striatum was 94+/-24 ml/ml. The results were compared with those of [123I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…Indeed, we have previously demonstrated that PE2I has a high affinity and a high specificity for DAT in the rat striatum (Emond et al, 1997;Guilloteau et al, 1998). Moreover, we have also shown in monkeys and in man (Kuikka et al, 1998) that this radioligand in vivo has a rapid and specific striatal accumulation, thus allowing the quantification of DAT based on the peak equilibrium method (Abi-Dargham et al, 1994). The binding of PE2I appears, therefore, to be a very efficient index of the loss of nigrostriatal dopaminergic neurons.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Indeed, we have previously demonstrated that PE2I has a high affinity and a high specificity for DAT in the rat striatum (Emond et al, 1997;Guilloteau et al, 1998). Moreover, we have also shown in monkeys and in man (Kuikka et al, 1998) that this radioligand in vivo has a rapid and specific striatal accumulation, thus allowing the quantification of DAT based on the peak equilibrium method (Abi-Dargham et al, 1994). The binding of PE2I appears, therefore, to be a very efficient index of the loss of nigrostriatal dopaminergic neurons.…”
Section: Discussionmentioning
confidence: 92%
“…We have, therefore, recently developed a series of iodinated analogs of cocaine (Emond et al, 1997) and among them, (E)-N-(3-iodoprop-2-enyl)-2␤-carbomethoxy-3␤-(4Ј-methylphenyl) nortropane (PE2I) had high affinity and selectivity for DAT in vitro and in vivo in rats . Preliminary SPET studies in humans indicated that the maximal striatum/cortex contrast was obtained at 1 h postinjection (Kuikka et al, 1998). It therefore appeared that PE2I was an efficient compound for SPET exploration of DAT.…”
Section: Introductionmentioning
confidence: 95%
“…[17][18][19][20][21] The radioligand [ 125 I]epidepride ((S)-N-((1-ethyl-2-pyrrolidinyl)methyl)-5-iodo-2,3, dimethoxybenzamine) has a very high affinity for DA D 2 receptors, with very low non-specific binding, and has been widely used to label DA D 2 receptors in the human brain. 22,23 It also binds to DA D 3 22 [ 125 I]PE2I ((E)-N-(3-iodoprop-2E-enyl)-2␤-carbomethoxy-3␤-(4Ј-methylphenyl) nortropane) is a novel radioligand ligand having high selectivity and affinity for DAT, [24][25][26] and has been previously used for imaging DAT both in vitro and in vivo. [24][25][26][27] It has 30-and Ͼ60-fold selectivities in vitro over serotonin and noradrenalin transporters, respectively, 25,26 which makes it far superior to older cocaine derivatives like ␤-CIT, frequently used in previous in vivo studies.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 It also binds to DA D 3 22 [ 125 I]PE2I ((E)-N-(3-iodoprop-2E-enyl)-2␤-carbomethoxy-3␤-(4Ј-methylphenyl) nortropane) is a novel radioligand ligand having high selectivity and affinity for DAT, [24][25][26] and has been previously used for imaging DAT both in vitro and in vivo. [24][25][26][27] It has 30-and Ͼ60-fold selectivities in vitro over serotonin and noradrenalin transporters, respectively, 25,26 which makes it far superior to older cocaine derivatives like ␤-CIT, frequently used in previous in vivo studies. Such radioligands in human post-mortem whole hemispheric autoradiography provide high resolution images from different brain levels, to compare with in vivo studies (ie, PET and SPET) and enable a more detailed study of various structures.…”
Section: Introductionmentioning
confidence: 99%
“…The radioligand has also been widely used in both preclinical and clinical studies; a PubMed search in January 2010 shows that 123 I-FP-CIT currently is mentioned in over 275 scientific papers. 123 I-labeled N-(3-iodoprop-2E-enyl)-2-b-carbomethoxy3b-(4-methylphenyl), named PE2I (MAP Medical Technologies), was synthesized in 1997 (8), and a dosimetry study in humans was published in 1998 (9). The ligand has about a 30-fold higher affinity for DAT than for SERT (Table 1), and because of its lower affinity to DAT 123 I-PE2I has faster kinetics than 123 I-FP-CIT, with a striatal peak time between 30 and 60 min.…”
mentioning
confidence: 99%